ENDOTHELIAL-SPECIFIC OVEREXPRESSION OF MUTATED INSULIN-LIKE GROWTH FACTOR-1 RECEPTORS (IGF-1R) ENHANCES ENDOTHELIAL INSULIN SENSITIVITY AND VASCULAR HYDROGEN PEROXIDE GENERATION. (21st November 2014) - Shah, P; Viswambharan, H; Gatenby, VK; Imrie, H; Haywood, N; Galloway, S; Sengupta, A; Cubbon, RM; Gage, M; Skromna, A; Makova, N; Grant, P; et al.
Abstract : Expression of Insulin-like growth factor-1 receptor (IGF-1R) and hybrid receptors formed between IGF-1R and insulin receptor (IR) in the vascular endothelium may be contributing factors to initiation of insulin resistance. The hypothesis that the IGF-1R acts as a negative regulator of insulin sensitivity and NO bioavailability in the endothelium is further investigated. Mice expressing non-functional, mutated human IGF-1R (K1003R) on the vascular endothelium (mIGFREO) under the control of Tie2 promoter-enhancer were generated. mIGFREO demonstrated no significant abnormalities in body and organ weight, as well as blood pressure compared to the wild type (WT) littermates. mIGFREO mice demonstrated preserved glucoregulation but showed a significant enhancement of whole body insulin sensitivity. Total hybrid expression was increased in the mIGFREO endothelial cells compared to WT controls, as well as the activated tyrosine phosphorylated insulin receptor (IRpY1328). Free fatty acid levels were lower in mIGFREO mice compared to WT littermates. Endothelial function assessed by vasorelaxation of aorta to acetylcholine remained unchanged between mIGFREO and WT littermates. The basal level of eNOS phosphorylation was enhanced in the mIGFREO endothelial cells compared to WT littermates. Nevertheless, mIGFREO aorta was significantly resistant to the vasodilatory effect of insulin. Interestingly, superoxide anion production was decreased among the mIGFREO mice compared to the WT littermate controls. Protein ex pression of NOX2, a source of superoxide anion generation was found to be significantly reduced, with a concomitant increase in NOX4 expression. These data suggest that mutation of endothelial IGF-1R demonstrates divergent effects on whole body and vascular endothelial insulin sensitivity.